Peningkatan Kesadaran Kesehatan Masyarakat Desa Mluweh: Pengukuran Tekanan Darah dan Edukasi Kesehatan - Khoiril Anam; Febry Putra Rochim; Safira Chairani Dimarti; Puput Ediyarsari; Ayu Nur Hidayah; M. Syahrul Muafi (Universitas Negeri Semarang, 2026)
Hypertension remains a public health problem in Indonesia, affecting both the elderly and those of productive age. Low awareness of the importance of health check-ups and a healthy lifestyle is a key contributing factor. This activity, organized by UNNES Community Service Program GIAT 12 students, was held in Mluweh Village, East Ungaran District, with the aim of increasing community awareness and participation in hypertension prevention efforts through an educational and participatory approach. Three main programs were implemented: a fun walk with students from MTs Mujahidin, blood pressure measurements for the elderly and school-age children, and group exercise with the community. The methods used included field observation, focus group discussions, health education, and two blood pressure measurements as a form of screening. The results of the activity demonstrated high community participation, with the majority of children having normal blood pressure and the elderly having low blood pressure. The program also demonstrated that simple physical interventions such as fun walks and exercise are well-received and have the potential to increase long-term health awareness. This activity provides recommendations for routine screening and the ongoing integration of healthy lifestyle education into community and school activities.